2020
DOI: 10.1177/0095399720915293
|View full text |Cite
|
Sign up to set email alerts
|

Side-Effects of Representation: Measuring the Impact of Representative Hiring on Employment Discrimination Complaints

Abstract: Since 1978, the government has been implementing programs to combat the underrepresentation of minorities in federal employment. However, representative bureaucracy literature has done little to examine the impact these initiatives are having on the workplace. This article examines the relationship between changes in representation and discrimination complaints. Increases in the ratio of minority and female employees predict an increase in the rates of race and sex-discrimination complaints, respectively. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…For example, during the latest census of law enforcement personnel prepared by the Bureau of Justice Statistics, 37.9% of all federal law enforcement officers are non-White, in comparison to just 16.1% of all state highway or patrol officers and 28.5% of all municipal police officers, mostly attributable to an increase in the percentage of Asian and Hispanic/Latino federal officers during the past couple of decades (Brooks 2019;Bureau of Justice Statistics 2020;Hyland and Davis 2019). Although this may appear encouraging at first, studies on workplace discrimination have shown that improved rates of minority representation within an organization are also associated with higher degrees of racebased discrimination (Alteri 2020;Rubin and Alteri 2019), truncating the careers of otherwise qualified minority candidates regardless of intergovernmental level (Bolton 2003;Gau, Paoline, and Roman 2021;Jollevet 2008;Schroedel et al 1994;Wilson and Wilson 2014).…”
Section: Structural Racismmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, during the latest census of law enforcement personnel prepared by the Bureau of Justice Statistics, 37.9% of all federal law enforcement officers are non-White, in comparison to just 16.1% of all state highway or patrol officers and 28.5% of all municipal police officers, mostly attributable to an increase in the percentage of Asian and Hispanic/Latino federal officers during the past couple of decades (Brooks 2019;Bureau of Justice Statistics 2020;Hyland and Davis 2019). Although this may appear encouraging at first, studies on workplace discrimination have shown that improved rates of minority representation within an organization are also associated with higher degrees of racebased discrimination (Alteri 2020;Rubin and Alteri 2019), truncating the careers of otherwise qualified minority candidates regardless of intergovernmental level (Bolton 2003;Gau, Paoline, and Roman 2021;Jollevet 2008;Schroedel et al 1994;Wilson and Wilson 2014).…”
Section: Structural Racismmentioning
confidence: 99%
“…Up to this point, nearly all the research on race-based discrimination in policing has focused on Black/Afri-can American officers, with Hispanics/Latinos, Asians, and other minority subgroups receiving very little to no consideration (e.g., Carter 1986;Gallardo 2020;Gau, Paoline, and Roman 2021;Holder, Nee, and Ellis 2000;Schroedel et al 1994;Yu 2022b). While there is basis for this targeted approach-for example, criminal justice reform initiatives such as President Johnson's Commission on Law Enforcement and Administration of Justice (1967) and President Obama's Task Force on 21st Century Policing (2015) were both enacted during periods of crisis between the police and the Black communities, respectively and concentrated on improving racial diversity in the police force with Black/African American officers (Skogan 2018)-race-based discrimination can extend to all race or ethnic subgroups, although research found that racial minorities were more likely to perceive workplace discrimination than White employees (Alteri 2020;Bradbury, Battaglio, and Crum 2010;Lee 2020;McCord et al 2018;Ortega et al 2012;Triana, Del Carmen, and Pieper 2015;Yu 2022a). For example, Carter (1986) and Gallardo (2020) reported in their studies on Hispanic police officers' workplace environment that race-based discrimination was prevalent throughout the department's recruitment, hiring, and promotion practices and this negatively impacted non-White officers.…”
Section: Structural Racismmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Alteri (2020) examined the relationship between changes in the representation of different groups and complaints of discrimination in the federal public service of the United States. She found that the rising ratios of minority employees and women led to higher rates of complaints of racial and gender discrimination.…”
Section: Introductionmentioning
confidence: 99%